2015
DOI: 10.1002/ptr.5546
|View full text |Cite
|
Sign up to set email alerts
|

Hedera nepalensis K. Koch: A Novel Source of Natural Cancer Chemopreventive and Anticancerous Compounds

Abstract: Traditional medicinal plants are often used for both the prevention and the treatment of local diseases. Taking into consideration the medicinal importance of Hedera nepalensis within local Pakistani traditions, the present study was undertaken to analyze the in vitro cancer chemopreventive and cytotoxic properties of the plant. The in vitro cancer chemopreventive testing was performed using nitrite assay, NFκB assay, aromatase assay, and quinone reductase 1 (QR1) assay. The cytotoxic potential was evaluated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
(33 reference statements)
3
6
0
2
Order By: Relevance
“…Phenolic compounds act as good electron donors and have the potential to reduce the Fe 3+ ion to the Fe 2+ ion. In reducing the power assay, FXE and FXB demonstrated the highest reducing potential with 16.2 AE 3.1 and 16.7 AE 2.8 mg GAE per mg sample respectively which is again in agreement with Jafri et al 42 The substantial antiradical capability of the ethyl acetate fraction might be due to the elevated polyphenols quantities. 39 This is in agreement with preceding information reported by Sajid et al 43 who suggested that the medicinal plants possess avonoids and polyphenols and it is due to these that they show antioxidant abilities, as these antioxidants are well established for their radical scavenging activities.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Phenolic compounds act as good electron donors and have the potential to reduce the Fe 3+ ion to the Fe 2+ ion. In reducing the power assay, FXE and FXB demonstrated the highest reducing potential with 16.2 AE 3.1 and 16.7 AE 2.8 mg GAE per mg sample respectively which is again in agreement with Jafri et al 42 The substantial antiradical capability of the ethyl acetate fraction might be due to the elevated polyphenols quantities. 39 This is in agreement with preceding information reported by Sajid et al 43 who suggested that the medicinal plants possess avonoids and polyphenols and it is due to these that they show antioxidant abilities, as these antioxidants are well established for their radical scavenging activities.…”
Section: Discussionsupporting
confidence: 90%
“…This assay is quantitative and based upon the number of AAE (mg mg À1 of extract). In this investigation FXE showed the highest total antioxidant ability (26.3 AE 2.4 mg AAE per mg sample), which was also observed by Jafri et al, 42 reporting that the ethyl acetate fraction of the aerial parts of Hedera nepalensis possess signicant total antioxidant capabilities. Phenolic compounds act as good electron donors and have the potential to reduce the Fe 3+ ion to the Fe 2+ ion.…”
Section: Discussionsupporting
confidence: 86%
“…For DPPH free radical scavenging activity, the described protocol of Abbasi et al [18] was used. The method of Jafri et al [19] was used for estimation of TAC and TRP. Briefly, 0.1 ml of callus extract was mixed with 1 ml of reaction mixture containing sulfuric acid (0.6 M), sodium phosphate (28 mM) and ammonium molybdate (4 mM) and incubated for 90 min in a water bath at 95 °C.…”
Section: Methodsmentioning
confidence: 99%
“…A decoction is used to treat skin diseases. Significant cancer chemo-preventative and cytotoxic properties have been demonstrated (Jafri et al 2016). It is also reported to be an important folk medicine for the treatment of diabetes.…”
Section: Medicinal Foods In the Dietmentioning
confidence: 99%